From Jaka Tarub to Jeong Jae-Hyun: Reimagining Indonesian Folktales in Popular Settings - Nugrahani, Dyah (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This study investigates how students reimagine the Indonesian folk tale Jaka Tarub within a contemporary Korean drama framework, highlighting reimagination as both a cultural and pedagogical practice. Unlike prior research that largely examines professional adaptations, this study focuses on student-led reimagination, emphasizing the creative and interpretive decisions made in an educational setting. Adopting a qualitative descriptive design, data were collected from student-produced narratives and follow-up interviews. Analysis applied Spradley’s ethnographic model, Hutcheon’s adaptation theory, and Purnomo et al.’s typology of mutation and presentness, supported by Dolmaya’s translation frameworks. The findings reveal three major functions of reimagination: stylistic (genre shifts into Korean drama conventions), methectic (reader immersion through emotional engagement), and cultural (symbolic translation, e.g., “rice” becoming “cellphone data”). These functions were accompanied by markers of mutation and presentness across textual, visual, and operative dimensions. The study contributes originality by documenting how emerging authors creatively bridge local heritage and global pop culture, demonstrating narrative reimagination as a form of transadaptation that preserves thematic essence while recontextualizing symbols for modern relevance. Pedagogically, the research shows that reimagination enhances cultural, narrative, and media literacies, while fostering intercultural awareness and critical engagement with tradition. It positions student-led adaptation not merely as a classroom exercise, but as a strategy for cultural revitalization and an innovative approach to literature teaching.